Effect of fluorination on the performance of poly(thieno[2, 3-f]benzofuran-co-benzothiadiazole) derivatives1. Issue 38 (30th April 2015) - Cui, Ruili; Fan, Ling; Yuan, Jun; Jiang, Lihui; Chen, Guohui; Ding, Yanhuai; Shen, Ping; Li, Yongfang; Zou, Yingping
<x xml:space="preserve">Abstract</x> Three polymers named PTBFBT-0F, PTBFBT-1F, PTBFBT-2F were synthesized, and the effects of the different numbers of fluorine atoms on the photophysics and photovoltaic properties were investigated. A PCE of 5% with PTBFBT-2F as the donor was obtained.